Hearing habits and hearing knowledge among music tertiary students - Leong, Yee Kay; Indra, Selvarajah; Loo, Fung Chiat (Human Resource Management Academic Research Society, 2022)
With the advancement of modern technology, almost everyone possesses at least one personal listening devices (PLDs) for music listening especially music tertiary students. Music tertiary students listen to music more than the other students due to the nature of their profession. Therefore, the current research aims to describe the hearing habits and hearing knowledge on the safe usage of PLDs among music tertiary students. The participants are comprised of 140 music tertiary students. They were asked to answer online questionnaires regarding the intensity and duration of PLDs used, the environment in which the PLDs were used, and knowledge towards the secure restriction on the PLDs usage. The results indicated that the majority of them listening to the PLDs every day between 15 minutes and 30 minutes at the moderate listening level with a volume control level set at 41%-60%. The overall correlation between hearing habits and hearing knowledge is high. The study also indicated that some music tertiary students lack awareness on the safe use of PLDs. It is important for children to have this awareness as early as possible. Teachers and professionals play important roles in educating children on healthy hearing habits and encouraging parental participation on this matter.